2015
DOI: 10.7314/apjcp.2015.16.15.6795
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Epidemiological Assessment of Breast Cancer Incidence and Mortality in Kazakhstan, 1999-2013

Abstract: Breast cancer incidence and mortality in Kazakhstan are considered to be increasing but exact statistics have hitherto been lacking. The present study was therefore undertaken to retrospectively assess data for the whole country, accessed from the central registration office, for the period 1999-2013. Age standardized data for incidence and mortality were generated and compared across age groups. It was determined that during the studied period 45,891 new cases of breast cancer were registered and 20,122 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…In the study period, about 20% of new cases and deaths from breast cancer were registered in the two large cities of Kazakhstan (1, 2). These cities host more medical organizations than other regions of the country; therefore, the changes in epidemiological indicators allow assessing the efficiency of national mammalogical screening in the country, also in the megapolises.…”
Section: Discussionmentioning
confidence: 99%
“…In the study period, about 20% of new cases and deaths from breast cancer were registered in the two large cities of Kazakhstan (1, 2). These cities host more medical organizations than other regions of the country; therefore, the changes in epidemiological indicators allow assessing the efficiency of national mammalogical screening in the country, also in the megapolises.…”
Section: Discussionmentioning
confidence: 99%
“…Astana and Almaty showed a high incidence rate in Kazakhstan. Ethnicity and compliance with screening recommendation affect breast cancer [24]. A study in India showed that the age standardized incidence rates of breast cancer increased from 24.8 in 1988 to 41.0 in 2012 in Delhi.…”
Section: Discussionmentioning
confidence: 99%
“…Large variations in both the incidence and mortality from breast cancer have been observed between the regions of Kazakhstan. Nur-Sultan, Almaty, and the four central and eastern regions of Kazakhstan have been reported to have the highest mortality from breast cancer [6]. Recent studies have shown some decrease in mortality from breast cancer in large cities of Kazakhstan in parallel with an increase in proportion of cancers diagnosed at early stages [16].…”
Section: оригинальные статьиmentioning
confidence: 99%
“…Several studies have reported an increase in the incidence of breast cancer in Kazakhstan [6,11,15,24]. The latest data suggest that the age-standardized incidence of breast cancer is 37.2 per 100,000 while cause-specific mortality is 14.8 per 100 000 [25].…”
Section: Introductionmentioning
confidence: 99%